Use of Eye Behavior With Visual Distraction for Attention Training in VR - Li, Yi Joy; Ramalakshmi, Pranathi Ayyalaraju; Mei, Chao; Jung, Sungchul (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
Concentration and attention skills are critical to human beings in almost every area of society, including school, work, and relationships. Especially, improving and increasing attention skills for certain people with social impairments such as Autism Spectrum Disorders, will assist their intervention and benefit their life quality. Virtual reality (VR) with a behavioral analysis system can help attention training with more customized scenarios for interaction and a fully controllable virtual environment that is often not available in real life. In the current phase, a system prototype was developed and a preliminary study with young adult participants was conducted to collect the baseline and validate the design. A within-subject design was used to embed four different training strategies in the training session. A total of 20 participants were involved in the preliminary experiment. The results of the data analysis show that even though eye gazing on certain objects decreased as expected, the total distraction time was rather on the opposite trend. The results have brought up new insights into the study and will inspire more improvement in future steps.